Rain rate and rain attenuation analysis over millimeter wave in microwave 5G/6G link systems - Tashan, Waheeb; Yaşar, Halimcan; Shayea, Ibraheem; El Saleh, Ayman A. (My University, 2024)
Future mobile communication systems require high data rate, efficient capacity and more secure communication system. However, 5G/6G millimeter waves (mm-Waves) are introduced as the promising solution method for the network operators. In contrast, rainfall may severely affect negatively on signal quality since the wave length of 5G/6G frequency spectrum almost near to raindrops sizes. Thereby, deteriorating system performance. This study comprehensively surveys rain rate (RR) and rain attenuation (RA) using mm-Waves in microwave 5G/6G link systems. Moreover, most of the studies are implemented in tropical and equatorial regions due to heavy rain which increases the rain attenuation. Furthermore, different models with various operating frequencies were applied to investigate the measured/or predicted dataset. Therefore, these models were compared to investigate their effectiveness. However, several models may not working perfectly for all regions. Thus, while implementing 5G/6G radio frequency (RF) links, using real measurements gives more reliable results than using models in terms of the RR and RA.
Keywords: Rain Rate; 5G/6G; Microwave; Conference